J Sur Anesth Res 2020
DOI: 10.47363/jsar/2020(1)103
|View full text |Cite
|
Sign up to set email alerts
|

Fast Track (Acerto) in Elderly Patients for Hip Orthopedic Surgeries. Ten Years of Experience

Abstract: In 2010, we started implementing the ACERTO project in a hospital in the northeast of the Brazilian Public Health (SUS) after five weeks with all stakeholders involved in the departments of Anesthesiology, Orthopedics, Geriatrics, Nutrition, Nursing, Physiotherapy, Psychology and Social Service. In the same way as in other hospitals, the implementation of fast track surgery was not obtained by all departments and all health professionals. The use of ACERTO protocol with clinical measures of accelerating patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Blockade of the lumbar and sacral plexuses improved postoperative analgesia in elderly patients with hip and femur fractures, reducing the side effects of opioids, and thus facilitating the rapid recovery process. 1,7,21,22 The average duration of analgesia was 22 hours, similar to other studies with the same type of surgery.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Blockade of the lumbar and sacral plexuses improved postoperative analgesia in elderly patients with hip and femur fractures, reducing the side effects of opioids, and thus facilitating the rapid recovery process. 1,7,21,22 The average duration of analgesia was 22 hours, similar to other studies with the same type of surgery.…”
Section: Discussionsupporting
confidence: 76%
“…This study was based on the recently published 1,226 patients. 1 Due to the fact that the study was retrospective, the Free and Informed Consent Term was released. The patients also were informed about risk of spinal anesthesia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, twelve years after the original design, CBC and BRASPEN jointly published the ACERTO Directive of perioperative nutritional interventions 31 . Over time, new anesthesiology researchers also started to propagate the ACERTO publications 32 , 33 and events (LEI, JSJ).…”
Section: Introductionmentioning
confidence: 99%
“…Ludwig et al, in Southern Brazil, reported that ACERTO showed good results and that modifications of the perioperative care protocol should be encouraged, as they speed patient recovery 63 . Imbelloni et al published several studies reporting good results in orthopedic and elderly patients with modifications to the traditional protocol, including abbreviated preoperative fasting, reduction of intravenous fluids, and blockage analgesia 32 , 64 - 66 . Ravanini et al reported the use of drinks containing carbohydrates and whey protein two hours before anesthetic induction, improving postoperative insulin resistance in patients undergoing video cholecystectomy 67 .…”
Section: Introductionmentioning
confidence: 99%